Clinical characterization of children with resistant airflow obstruction, a multicenter study. (3rd June 2019) - Krishnan, Sankaran; Dozor, Allen J; Bacharier, Leonard; Lang, Jason E; Irvin, Charles G.; Kaminsky, David; Farber, Harold J; Gerald, Lynn; Brown, Mark; Holbrook, Janet T; Wise, Robert A; Ryu, Julie; et al.
ABSTRACT: Objective : To characterize a cohort of children with airflow limitation resistant to bronchodilator (BD) therapy. Methods : Pulmonary function tests performed in children 6–17 years of age at 15 centers in a clinical research consortium were screened for resistant airflow limitation, defined as a post-BD FEV1 and/or an FEV1 /FVC less than the lower limits of normal. Demographic and clinical data were analyzed for associations with pulmonary function. Results : 582 children were identified. Median age was 13 years (IQR: 11, 16), 60% were males; 62% were Caucasian, 28% were African-American; 19% were obese; 32% were born prematurely and 21% exposed to second hand smoke. Pulmonary diagnoses included asthma (93%), prior significant pneumonia (28%), and bronchiectasis (5%). 65% reported allergic rhinitis, and 11% chronic sinusitis. Subjects without a history of asthma had significantly lower post-BD FEV1 % predicted ( p = 0.008). Subjects without allergic rhinitis had lower post-BD FEV1 % predicted ( p = 0.003). Children with allergic rhinitis, male sex, obesity and Black race had better pulmonary function post-BD. There was lower pulmonary function in children after age 11 years without a history of allergic rhinitis, as compared to those with a history of allergic rhinitis. Conclusions : The most prevalent diagnosis in children with BD-resistant airflow limitation is asthma. Allergic rhinitis and premature birth are common co-morbidities. Children without a history of asthma, as well as those with asthma but no allergic rhinitis, had lower pulmonary function. Children with BD-resistant airflow limitation may represent a sub-group of children with persistent obstruction and high risk for life-long airway disease.